PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SIKAP YANG TERARAH PADA PEMIKIRAN YANG BERAGAM TERHADAP PERFORMA KREATIVITAS GURU DI SEKOLAH SMA ST MARIA MEDAN - Regina Sipayung (Universitas Negeri Medan, 2020)
The problems of this research are the lack of students who enroll to SMA St Maria Medan and the less amount of entire students from Classes IX – XII. The one way leadership of the principal of SMA St Maria Medan and not open to receive new ideas from teachers cause the teachers become not creative and not variative in performing learning teaching processes. They are also not active in attending events held by the school. The objectives of this research are to analyze the effects of the principal’s leadership and behavior oriented to various thoughts on the teachers’ creativity performance. Data were collected by using questionnaires and interviewing the principal, teachers, and 30 (thirty) administrative staffs. Data were analyzed by using simple linear regression. The research findings show that there is a significant effect of the principal’s leadership on the teachers’ creativity performance; that is 0.538 (pretty strong) and there is a significant effect of the principal’s various thoughts on the teachers’ creativity performance; that is 0.78 (very strong).Keywords: Principal’s leadership, various thoughts, creativity performance